Cognitive, Affective, and Desire Factors in Predicting Domestic Tourism Intention: The Model Application of Goal-Directed Behavior - Ericko Grady; Sabrina Sihombing (Politeknik Negeri Bandung, 2022)
Tourism is one of the sectors that has been directly impacted by the COVID-19 pandemic. The decline in the number of domestic and foreign tourists has an impact on the country's economy. Therefore, this study aims to test the theory of Goal Directed Behavior in predicting the intention to visit local tourists during the Covid-19 pandemic. This study uses a quantitative approach and uses a purposive sampling strategy to obtain data through the distribution of online surveys. There were 209 respondents who met domestic travel requirements in the past year. Structural Equation Modeling (SEM) is used as an analytical tool in testing research hypotheses. The results of the analysis showed that the relationship between attitudes, subjective norms, perceived behavioral control, positive anticipated emotions, negative anticipated emotions, was mediated by desire towards intention.